AD, Volume 30, n° 1 & 2, 2005 - Full Issue - journal system, (Africa Development, 2022)
Contents Maladjusted African Economies and Globalisation Thandika Mkandawire .................................1 Shared Governance and Leadership in African Universities: Experiences from Mzuzu University, Malawi and Amoud University,Somaliland Mohamed A. Nur-Awaleh and Dorothy M. Mtegha .............................34 The Growth of Islamic Learning in Northern Ghana and Its Interaction with Western Secular Education Abdulai Iddrisu ..................................53 Graduates'Perception of University Programmes and Their Relevance to Employment: A Study University of Nairobi Graduates ( 1991 - 1998) Gerald N. Kimani .................................68 Supporting University ICT Developments: The Makerere University Experience Francis Frederick Tusubira ..........................86 Globalisation, ICTs, and the New Imperialism: Perspectives on Africa in the Global Electronic Village (GEV) Yunusa Z. Ya'u ...................................98 L'Union africaine comme réponse africaine au défi de la mondialisation Reine Djuidje Kouam ...................................125 NEPAD and the Digital Divide: Silent Marginalised Minorities in the age of ICT: The Case of Botswana Sethunya Tshepho Mphinyane ................................152 Connecting African Activism with Global Networks: ICT's and South African Social Movements Herman Wasserman .................................163